Star trek: picard: countdown ebook - Beyer, Kirsten (Star Trek: Picard (2019)., 2020)
Witness the events leading to the new CBS All Access series PICARD in this graphic novel where new characters are introduced and secrets will be revealed. Before he retired to his vineyard, Jean-Luc Picard was the most decorated admiral in Starfleet. Then one mission changed his life forever. What could make this dedicated and disciplined leader question his calling? Author: Kirsten Beyer, Mike Johnson . Illustrator: Angel Hernandez . ® & © 2020 CBS Studios Inc. STAR TREK and related marks are trademarks of CBS Studios Inc. All Rights Reserved.